External wealth of nations and systemic risk - Andrieş, Alin Marius; Chiper, Alexandra Maria; Ongena, Steven; Sprincean, Nicu (Journal of Financial Stability, 2024)
External imbalances played a pivotal role leading to the global financial crisis and were an important cause of turmoil. While current account (flow) imbalances narrowed in the aftermath of the crisis, the net international investment position (NIIP) (stock) imbalances persisted. This study explores the implications of countries’ net foreign positions on systemic risk. Using a sample of 470 banks located in 49 advanced economies, emerging countries, and developing economies over 2000–2020, we find robust empirical evidence that banks can reduce their systemic risk exposure when the countries in which they are incorporated improve their NIIPs and maintain creditor status vis-à-vis the rest of the world. However, only the equity component of the NIIP is responsible for this outcome, whereas debt flows are not significant. Similarly, we find that the mitigating effect of an external balance sheet on systemic risk is derived from valuation gains rather than from the incremental net acquisition of assets or liabilities represented by the current account. Our findings are particularly relevant for policymakers seeking to improve banks’ resilience to adverse shocks and maintain financial stability.